Integration of TDEM and HVSR surveys for water resources investigation in arid regions: The case of Horombe plateau, Madagascar - Paschetto, Arianna; Vergnano, Andrea; Caselle, Chiara; Comina, Cesare; Benente, Luigi; Bono, Edoardo; Fenoglio, Taddeo Maria; Fontanella, Francesca; Vianello, Davide; Bonetto, Sabrina Maria Rita (Journal of applied geophysics, 2025)
The increasing threat of droughts, due to climate variability and rising water demands, is further exacerbated by the lack of hydrogeological knowledge of remote areas such as Southern Madagascar. This study aims to showcase the utility of cost-effective and portable geophysical methods alongside with detailed geological and hydrogeological investigations to enhance water resource exploration in arid regions. For this purpose, integration of Horizontal-to-Vertical Spectral Ratio (HVSR) and Time Domain Electromagnetic Method (TDEM) has been adopted to investigate a 5 km2 area, with 41 survey points, in a zone of the Horombe plateau, in South Madagascar, remote and mostly unknown from the geological point of view. Considering the dominant frequencies of HVSR, the TDEM resistivity model and the few available literature and field geological data (a water well sampling campaign), a geological interpretation of geophysical data was performed to assess the distribution and extent of water resources. The proposed geological/hydrogeological interpretation consists of a laterite cover, hosting irregular and ephemeral aquifers, a saprolite layer, hosting the main aquifer, and a gneiss bedrock. According to the results of this study, three new water wells were drilled where geophysical data detected the thickest aquifer. The wells validated the proposed geological model and confirmed the presence of main aquifers in the bottom part of saprolite layer and thinner aquifers in the lateritic cover. The results of the study offer a framework for the application of easy-to-operate geophysical solutions for water resources management in remote arid areas with scarcity of available data. The paper also discusses the limitations and uncertainties in geophysical data interpretation, particularly regarding the achievable investigation depth. [Display omitted] •Acquisition of data with Time Domain Electromagnetic Method (TDEM) and passive seismic methods (HVSR)•Definition of a procedure for identifying water resources in arid areas•Provided new geological insights into poorly studied areas of South Madagascar•Selected portable geophysical techniques focusing on remote areas•Defined a hydrogeological model for a drought-vulnerable village